Development and evaluation of a chronotherapeutic drug delivery system of torsemide - Songa Ambedkar Sunil; Nali Sreenivasa Rao; Meka Venkata Srikanth; Michael Uwumagbe Uhumwangho; Kommana Srinivas Phani Kumar; Kolaplli Venkata Ramana Murthy (Universidade de São Paulo, 2011)
The objective of this study was to prepare and evaluate chronotherapeutic drug delivery systems (ChrDDs) of torsemide. Compression coated tablets (CCT) containing torsemide in the core tablet were prepared by the compression coating technique with different grades of polyethylene oxide (PEO WSR 301 & 1105). The optimized formulations were characterised for tabletting parameters and drug polymer interaction by Fourier-Transform Infrared Spectroscopy (FTIR).The hardness of all the CCT using PEO WSR 301 & PEO WSR 1105 were in the range 6-8 kg/cm² & 5.5 to 7 kg/cm² respectively. Their friability values were <0.3%. All the CCT showed a clear lag time but finalized as per the predetermined lag time. As the amount of PEO was increased in the outer layer the drug released was delayed. The drug content of all the CCT was >99%. The FTIR studies showed no interaction throughout the process of development. Formulations of F7 and of P7 were considered optimized formulations since they yielded a predetermined lag time of 6h before burst release. Hence, these formulations can be exploited to achieve chronotherapeutic drug delivery systems of Torsemide for the treatment of hypertension at the time the patient needs it. O objetivo deste estudo foi preparar e avaliar sistemas cronoterapêuticos de liberação de fármacos (ChrDDs) de torsemida. Comprimidos revestidos por compressão (CCT) contendo torsemida no (núcleo) foram preparados pela técnica de revestimento por compressão, com diferentes categorias de óxido de polietileno (PEO WSR 301 & 1105). As formulações otimizadas foram caracterizadas por parâmetros de compressão e interação fármaco polímero por Infravermelho com Transformada de Fourier (FTIR). A dureza dos CCT utilizando PEO WSR 301 e PEO WSR 1105 foi entre 6-8 kg/cm² e 5,5 a 7 kg/cm², respectivamente. Os valores de friabilidade foram <0,3%. Todos os CCT mostraram claro tempo de retardo, mas finalizaram de acordo com o tempo de retardo pré-determinado. À medida que a quantidade de PEO aumentava na camada mais externa, a liberação do fármaco era retardada. O teor de fármaco em todos os CCT foi >99%. Os estudos de FTIR mostraram que não h[a interação durante o processo de desenvolvimento. As formulações F7 e P7 foram consideradas otimizadas, uma vez que resultaram em tempo de retardo pré-determinado de 6 h antes da liberação por meio de explosão. Dessa forma, estas formulações podem ser exploradas para se obter sistemas de liberação.